Transfery budżetowe w świetle literatury i praktyki amerykańskiej - Olejniczak, Jarosław (Intergovernmental Grants in American Literature and Practice, 2005)
Central government transfers to sub-national authorities budgets are more or less important in different countries. This article has to describe the basic models of intergovernmental grants. As the role of sub-national (regional or local) community differs, kinds of possible grants also differ. The decentralized system is based on general grants while centralized on the specific ones. Different purposes can be achieved through different grants - for e.g. grants can close a "fiscal gap" through the horizontal or vertical redistribution of founds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 64-74